2006
DOI: 10.1038/sj.jcbfm.9600269
|View full text |Cite
|
Sign up to set email alerts
|

CBF Changes Associated with Focal Ischemic Preconditioning in the Spontaneously Hypertensive Rat

Abstract: Experimental stroke models exhibit robust protection after prior preconditioning (PC) insults. This study comprehensively examined cerebral blood flow (CBF) responses to permanent middle cerebral artery (MCA) occlusion in spontaneously hypertensive rats preconditioned by noninjurious transient focal ischemia, using [ 14 C]iodoantipyrine autoradiography at varied occlusion intervals. Preconditioning was produced by 10-min occlusion of the MCA and ipsilateral common carotid artery under halothane anesthesia. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
41
0
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 45 publications
(44 citation statements)
references
References 58 publications
(98 reference statements)
1
41
0
2
Order By: Relevance
“…In spontaneously hypertensive rats, part of the IPC-induced tolerance has been attributed to improvement in blood flow over a period of several hours of permanent MCAO. 18 In the present model with transient MCAO, the decrease in LDF over lateral cortex in the ischemic core during the test MCAO was similar to that during each IPC occlusion. Although improved blood flow distribution in penumbra by IPC cannot be excluded, differences in intraischemic regional blood flow determined by autoradiography could not be detected during acute occlusion in rats previously conditioned with 3 10-minute bouts of MCAO.…”
Section: Effect Of Anestheticsmentioning
confidence: 75%
“…In spontaneously hypertensive rats, part of the IPC-induced tolerance has been attributed to improvement in blood flow over a period of several hours of permanent MCAO. 18 In the present model with transient MCAO, the decrease in LDF over lateral cortex in the ischemic core during the test MCAO was similar to that during each IPC occlusion. Although improved blood flow distribution in penumbra by IPC cannot be excluded, differences in intraischemic regional blood flow determined by autoradiography could not be detected during acute occlusion in rats previously conditioned with 3 10-minute bouts of MCAO.…”
Section: Effect Of Anestheticsmentioning
confidence: 75%
“…Depth and duration of anesthesia, important variables in studies of PC, 22,23 were closely monitored and kept constant in all experiments. Body temperature has powerful effects on NMDA-mediated brain injury.…”
Section: Discussionmentioning
confidence: 99%
“…These investigations have established that ischemic tolerance is associated with genetic, biochemical, and neurophysiological changes in neurons and glia that render the brain more resistant to ischemia. However, it has also been observed that tolerance-inducing stimuli improve microvascular perfusion or cerebral blood flow (CBF) in the postischemic brain (Dawson et al, 1999;Furuya et al, 2005;Hoyte et al, 2006;Nakamura et al, 2006;Zhao and Nowak, 2006). Although these studies have suggested that preconditioning protects cerebral blood vessels from the vasoparalysis induced by cerebral ischemia, the effects of preconditioning on cerebrovascular function and the specific contribution of vascular factors to the protection have not been determined.…”
Section: Introductionmentioning
confidence: 95%